Wear-resistant environment-friendly TPU for automobile foot mat and preparation method of wear-resistant environment-friendly TPU

By using wear-resistant and environmentally friendly TPU materials with carbon fiber and steel fiber composites and hollow glass microbeads in automotive foot pads, the problem of insufficient wear resistance and tensile strength of pure TPU materials in high shear environments is solved, and the problem of insufficient wear resistance and tensile strength of pure TPU materials in high shear environments is achieved. Higher wear resistance and tensile strength, and ensures the safety and environmental protection of the material.

CN119161720AActive Publication Date: 2024-12-20DONGGUAN ZHONGDING PLASTIC PRODUCTION CO LTD

Patent Information

Application Number
CN202411138180.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2024-12-20
Estimated Expiration
2044-08-19

AI Technical Summary

Technical Problem

Pure TPU materials have problems with insufficient tensile strength and wear resistance in automotive foot pad applications, resulting in deformation, fatigue and wear in high shear environments, affecting service life and anti-slip effect.

Method used

Using wear-resistant and environmentally friendly TPU materials composed of carbon fiber and steel fiber composites and hollow glass microbeads, the fiber composites and hollow glass microbeads are added through specific formulations and preparation methods, combining oligomer polyols and nanodioxide. Silicon, improves the wear resistance and tensile strength of the material.

Benefits of technology

It significantly improves the wear resistance and tensile strength of the car foot pads, extends the service life, and ensures safety and environmental protection through the use of low-toxic and environmentally friendly raw materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004999989820000051
    Figure BDA0004999989820000051
  • Figure BDA0004999989820000061
    Figure BDA0004999989820000061
Patent Text Reader

Abstract

The invention discloses wear-resistant and environment-friendly TPU for an automobile foot mat and a preparation method of the wear-resistant and environment-friendly TPU. The environment-friendly TPU is prepared from the following raw materials in parts by weight: 20 to 30 parts of diisocyanate, 50 to 80 parts of oligomer polyol, 30 to 45 parts of epoxy resin, 20 to 30 parts of a fiber compound, 10 to 15 parts of hollow glass beads, 5 to 8 parts of an amino silane coupling agent and 0.5 to 1 part of a catalyst. The fiber compound comprises carbon fibers and steel fibers, and the weight ratio of the carbon fibers to the steel fibers is 1: 1. The wear-resistant environment-friendly TPU material for the automobile foot mat has the advantages of being good in wear resistance and tensile strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of automobile floor mats, and in particular to a wear-resistant and environmentally friendly TPU for automobile floor mats and a preparation method thereof. Background Art

[0002] As a choice for anti-slip pads, TPU material has many favorable properties such as elasticity, hardness and adjustability. However, there are some problems with the application of pure TPU material in car mats. The first is the tensile strength. The tensile strength of pure TPU material is relatively low, which cannot fully meet the requirements of car mats in high shear working environment. Long-term continuous tensile and shear stress will cause deformation and fatigue of TPU material, reducing its service life. The second is the wear resistance problem. The wear resistance of pure TPU material is relatively low, which is difficult to meet the needs of long-term use of car mats. Under high-frequency friction, pure TPU material is prone to wear, abrasion or surface cracks, affecting its service life and anti-slip effect. These problems cause the performance of car mats to be unstable in high-shear working environment, and even lose the anti-slip function, affecting driving safety and ride comfort. Summary of the invention

[0003] In order to solve at least one of the above technical problems and develop a car floor mat with better wear resistance and tensile strength, the present application provides a wear-resistant and environmentally friendly TPU for car floor mats and a preparation method thereof.

[0004] In a first aspect, the present application provides a wear-resistant and environmentally friendly TPU for car mats, wherein the environmentally friendly TPU comprises the following raw materials by weight: 20-30 parts of diisocyanate, 50-80 parts of oligomer polyol, 30-45 parts of epoxy resin, 20-30 parts of fiber composite, 10-15 parts of hollow glass microspheres, 5-8 parts of aminosilane coupling agent and 0.5-1 part of catalyst; The fiber composite comprises carbon fibers and steel fibers, wherein the weight ratio of the carbon fibers to the steel fibers is 1:1.

[0005] By adopting the above technical scheme, the present application can solve the problems of poor wear resistance and tensile strength of car mats in the prior art, and provide a wear-resistant and environmentally friendly TPU for car mats with better wear resistance and tensile strength. When preparing wear-resistant and environmentally friendly TPU for car mats, the present application can prepare a car mat with excellent performance through a specific formula. When preparing car mats, the present application adds fiber composites and hollow glass microspheres, and the fiber composites are prepared by compounding carbon fibers and steel fibers. Therefore, the present application can better improve the wear resistance of car mats by using fiber composites composed of two components. On this basis, the present application also adds hollow glass microspheres. The addition of hollow glass microspheres can further improve the wear resistance of car mats, and the hollow structure of glass microspheres can provide strong tensile strength and light weight for car mats. In addition, the present application adds oligomer polyols, and the addition of oligomer polyols can provide better tensile strength for environmentally friendly TPU. At the same time, the raw materials used in the preparation of the car floor mats of the present application are all low-toxic and environmentally friendly raw materials. Therefore, the prepared car floor mats have the advantages of safety and environmental protection.

[0006] Optionally, the environmentally friendly TPU comprises the following raw materials by weight: 25-30 parts of isocyanate, 65-80 parts of oligomer polyol, 40-45 parts of epoxy resin, 25-30 parts of fiber composite, 12.5-15 parts of hollow glass microspheres, 7-8 parts of aminosilane coupling agent and 0.8-1 part of catalyst.

[0007] Optionally, the environmentally friendly TPU includes the following raw materials by weight: 28 parts of isocyanate, 75 parts of oligomer polyol, 43 parts of epoxy resin, 28 parts of fiber composite, 14 parts of hollow glass microspheres, 7.4 parts of aminosilane coupling agent and 0.9 parts of catalyst.

[0008] Optionally, the environmentally friendly TPU also includes 5-8 parts of silicon dioxide.

[0009] Optionally, the silicon dioxide is nano silicon dioxide; the particle size of the nano silicon dioxide is 5-10 nm.

[0010] By adopting the above technical scheme, the present application also adds nano-silicon dioxide when preparing the wear-resistant and environmentally friendly TPU for car mats. Nano-silicon dioxide has a large specific surface area and a small particle size. Therefore, the addition of nano-silicon dioxide can further improve the wear resistance of the prepared car mats, and nano-silicon dioxide and hollow glass microspheres can provide the car mats with strong tensile strength and wear resistance.

[0011] Optionally, the diameters of the carbon fibers and steel fibers are both 5-10 microns.

[0012] Optionally, the oligomer polyol is polycaprolactone polyol.

[0013] Optionally, the aminosilane coupling agent includes γ-aminopropyltrimethoxysilane.

[0014] Optionally, the catalyst comprises triethanolamine.

[0015] In a second aspect, the present application provides a method for preparing a wear-resistant and environmentally friendly TPU for a car mat, the preparation method comprising the following steps: S1, mixing and reacting the fiber composite, hollow glass microspheres and aminosilane coupling agent, the reaction temperature is 80-100°C, and the reaction time is 20-30min; S2, taking 2040% of the oligomer polyol, mixing it with the epoxy resin and the material obtained in step S1, and dehydrating it; S3, mixing diisocyanate, 60-80% oligomer polyol, and a catalyst, reacting at a reaction temperature of 65-75° C. for 1-2 hours to obtain a polyurethane prepolymer; S4, mixing the mixed material obtained in step S2, the polyurethane prepolymer obtained in step S3 and the remaining raw materials, reacting at a reaction temperature of 80-90° C. for 4-6 hours to obtain a TPU material, pressing the TPU material into a sheet, punching and forming, and obtaining the wear-resistant and environmentally friendly TPU sheet for the car mat.

[0016] By adopting the above technical solution, the present application can prepare a wear-resistant and environmentally friendly TPU for automobile floor mats with strong wear resistance and tensile strength, and the preparation method provided by the present application has the advantage of simple operation.

[0017] In summary, the present invention includes at least one of the following beneficial technical effects: 1. The present application can solve the problems of poor wear resistance and tensile strength of car mats in the prior art, and provide a wear-resistant and environmentally friendly TPU for car mats with better wear resistance and tensile strength. When preparing wear-resistant and environmentally friendly TPU for car mats, the present application can prepare a car mat with excellent performance through a specific formula. The present application adds fiber composites and hollow glass microspheres when preparing car mats, and the fiber composites are prepared by compounding carbon fibers and steel fibers. Therefore, the present application can better improve the wear resistance of car mats by using fiber composites composed of two components. On this basis, the present application also adds hollow glass microspheres. The addition of hollow glass microspheres can further improve the wear resistance of car mats, and the hollow structure of glass microspheres can provide car mats with strong tensile strength and light weight. In addition, the present application adds oligomer polyols, and the addition of oligomer polyols can provide environmentally friendly TPU with better tensile strength. At the same time, the raw materials used in the preparation of the car floor mats of the present application are all low-toxic and environmentally friendly raw materials. Therefore, the prepared car floor mats have the advantages of safety and environmental protection.

[0018] 2. The present application also adds nano-silicon dioxide when preparing the wear-resistant and environmentally friendly TPU for car mats. Nano-silicon dioxide has a large specific surface area and a small particle size. Therefore, the addition of nano-silicon dioxide can further improve the wear resistance of the prepared car mats, and nano-silicon dioxide and hollow glass microspheres can provide the car mats with strong tensile strength and wear resistance.

[0019] 3. The present application can prepare a wear-resistant and environmentally friendly TPU for automobile floor mats with high wear resistance and tensile strength, and the preparation method provided by the present application has the advantage of simple operation. DETAILED DESCRIPTION

[0020] The present application is further described in detail below with reference to the embodiments.

[0021] Diisocyanate: Sigma-Aldrich (Shanghai) Trading Co., Ltd.

[0022] Oligomeric polyol: polycaprolactone polyol, Shanghai Fuzhe Chemical Co., Ltd., purity 99%.

[0023] Bisphenol A epoxy resin: CAS No. 1675-54-3; purchased from Merck.

[0024] Carbon fiber: The average diameter is 5-10 microns.

[0025] Steel fiber: average diameter is 5-10 microns.

[0026] Hollow glass microspheres: Shanxi Hainuo Technology Co., Ltd., purity 99%.

[0027] Aminosilane coupling agent: γ-aminopropyltrimethoxysilane; purity 98%.

[0028] Catalyst: triethanolamine, Xingtai Xinlanxing Technology Co., Ltd., purity 99%.

[0029] Silicon dioxide: Yumu (Ningbo) New Materials Co., Ltd., micron-grade silicon dioxide 6 microns. Purity 99%.

[0030] Nano-silicon dioxide: Yumu (Ningbo) New Materials Co., Ltd., average particle size is 5-10nm. Specific embodiments

[0031] Example 1 This embodiment provides a wear-resistant and environmentally friendly TPU for car mats, and the environmentally friendly TPU includes the following raw materials by weight: 20 parts of diisocyanate, 50 parts of oligomer polyol, 30 parts of epoxy resin, 20 parts of fiber composite, 10 parts of hollow glass microspheres, 5 parts of aminosilane coupling agent and 0.5 parts of catalyst; The preparation method comprises the following steps: S1, mixing and reacting the fiber composite, hollow glass microspheres and aminosilane coupling agent, the reaction temperature is 80°C, and the reaction time is 20 minutes; S2, taking 20% ​​of the oligomer polyol, mixing it with the epoxy resin and the material obtained in step S1, and dehydrating it; S3, mixing diisocyanate, 80% of oligomer polyol, and a catalyst, reacting at a reaction temperature of 65° C. for a reaction time of 1 h to obtain a polyurethane prepolymer; S4, mixing the mixed material obtained in step S2 and the polyurethane prepolymer obtained in step S3, reacting at a reaction temperature of 80° C. for 4 hours to obtain a TPU material, pressing the TPU material into a sheet, punching and forming, and obtaining the wear-resistant and environmentally friendly TPU sheet for the car mat.

[0032] The catalyst in this embodiment is triethanolamine.

[0033] The aminosilane coupling agent in this embodiment is γ-aminopropyltrimethoxysilane.

[0034] The fiber composite is a composition of carbon fiber and steel fiber in a weight ratio of 1:1, and the average diameter of both fibers is 5-10 microns.

[0035] The oligomer polyol in this embodiment is polycaprolactone polyol.

[0036] The epoxy resin in this embodiment is bisphenol A epoxy resin.

[0037] Embodiment 2-5 The difference between Example 2-5 and Example 1 is that, when preparing the wear-resistant and environmentally friendly TPU for automobile floor mats, the weight proportions of the various components are different. The differences are shown in Table 1.

[0038] Table 1 - Differences between Examples 2-5 and Example 1 Element Example 1 Example 2 Example 3 Example 4 Example 5 Diisocyanates 20 23 25 28 30 Oligomeric polyols 50 63 65 75 80 Epoxy resin 30 38 40 43 45 Fiber composite 20 24 25 28 30 Hollow glass microspheres 10 12 12.5 14 15 Aminosilane coupling agent 5 6.5 7 7.4 8 catalyst 0.5 0.7 0.8 0.9 1 Comparative Examples 1-5 Comparative Example 1 The difference between this comparative example and Example 4 is that no fiber composite is added when preparing the wear-resistant and environmentally friendly TPU for automobile floor mats.

[0039] Comparative Example 2 The difference between this comparative example and Example 4 is that when preparing the wear-resistant and environmentally friendly TPU for automobile floor mats, an equal amount of carbon fiber is used to replace the fiber composite.

[0040] Comparative Example 3 The difference between this comparative example and Example 4 is that when preparing the wear-resistant and environmentally friendly TPU for automobile floor mats, an equal amount of steel fibers is used to replace the fiber composite.

[0041] Comparative Example 4 The difference between this comparative example and Example 4 is that, when preparing the wear-resistant and environmentally friendly TPU for automobile floor mats, no hollow glass microspheres are added.

[0042] Comparative Example 5 The difference between this comparative example and Example 4 is that, when preparing the wear-resistant and environmentally friendly TPU for automobile floor mats, no hollow glass microspheres and fiber composites are added.

[0043] Experimental testing Tensile strength: tested according to the method of GB / T 528-2009.

[0044] Abrasion resistance test: The abrasion resistance is tested according to the method of ASTM D10442008.

[0045] The experimental test results of Examples 1-5 and Comparative Examples 1-5 are shown in Table 2.

[0046] Table 2 - Experimental test results of Examples 1-5 and Comparative Examples 1-5 Result analysis: The difference between Examples 2-5 and Example 1 is that when preparing the wear-resistant and environmentally friendly TPU for car floor mats, the weight proportions of each component are different. Combined with the experimental test results in Table 2, it can be seen that the wear-resistant and environmentally friendly TPU for car floor mats prepared by Example 4 has better wear resistance and tensile strength.

[0047] The difference between Comparative Example 1 and Example 4 is that no fiber composite is added when preparing the wear-resistant and environmentally friendly TPU for automobile floor mats.

[0048] The difference between Comparative Example 2 and Example 4 is that, when preparing the wear-resistant and environmentally friendly TPU for automobile floor mats, an equal amount of carbon fiber is used to replace the fiber composite.

[0049] The difference between Comparative Example 3 and Example 4 is that, when preparing the wear-resistant and environmentally friendly TPU for automobile mats, an equal amount of steel fiber is used to replace the fiber composite. Combining the experimental test results of Example 4 and Comparative Examples 1-3, it can be seen that the fiber composite composed of two components can better improve the tensile strength and wear resistance of the prepared wear-resistant and environmentally friendly TPU for automobile mats.

[0050] The difference between Comparative Example 4 and Example 4 is that hollow glass microspheres are not added when preparing the wear-resistant and environmentally friendly TPU for automobile mats. The difference between Comparative Example 5 and Example 4 is that hollow glass microspheres and fiber composites are not added when preparing the wear-resistant and environmentally friendly TPU for automobile mats. Combining the experimental test results of Example 4 and Comparative Examples 4-5, it can be seen that when the fiber composite and the hollow glass microspheres are compounded and used, they can provide strong tensile strength and wear resistance for the wear-resistant and environmentally friendly TPU for automobile mats.

[0051] Embodiment 6-9 Example 6 The difference between this embodiment and embodiment 4 is that in this embodiment, when preparing the wear-resistant and environmentally friendly TPU for automobile floor mats, the total weight of the fiber composite and the hollow glass microspheres is 42 parts, wherein the weight ratio of the fiber composite to the hollow glass microspheres is 1.8:1.

[0052] Example 7 The difference between this embodiment and embodiment 4 is that in this embodiment, when preparing the wear-resistant and environmentally friendly TPU for automobile floor mats, the total weight of the fiber composite and the hollow glass microspheres is 42 parts, wherein the weight ratio of the fiber composite to the hollow glass microspheres is 1.9:1.

[0053] Example 8 The difference between this embodiment and embodiment 4 is that in this embodiment, when preparing the wear-resistant and environmentally friendly TPU for automobile floor mats, the total weight of the fiber composite and the hollow glass microspheres is 42 parts, wherein the weight ratio of the fiber composite to the hollow glass microspheres is 2.1:1.

[0054] Example 9 The difference between this embodiment and embodiment 4 is that in this embodiment, when preparing the wear-resistant and environmentally friendly TPU for automobile floor mats, the total weight of the fiber composite and the hollow glass microspheres is 42 parts, wherein the weight ratio of the fiber composite to the hollow glass microspheres is 2.2:1.

[0055] Table 3 - Experimental test results of Examples 6-9 Example Wear amount (mg) Tensile strength(MPa) Example 4 8.6 78.3 Example 6 8.9 77.3 Example 7 8.8 77.9. Example 8 8.3 79.2 Example 9 8.5 78.9 Result analysis: The difference between Examples 6-9 and Example 4 is that, when preparing the wear-resistant and environmentally friendly TPU for automobile floor mats, the total weight of the fiber composite and the hollow glass microspheres is the same, but the weight ratio of the fiber composite and the hollow glass microspheres is different. Combined with the experimental test data in Table 3, it can be seen that when the weight ratio of the fiber composite and the hollow glass microspheres is 2.1:1, the tensile strength and wear resistance of the wear-resistant and environmentally friendly TPU for automobile floor mats are better.

[0056] Examples 10-13 Example 10 The difference between this embodiment and embodiment 8 is that 5 parts of silicon dioxide are further added when preparing the wear-resistant and environmentally friendly TPU for automobile floor mats.

[0057] The preparation method is as follows: S1, mixing and reacting the fiber composite, hollow glass microspheres, silica and aminosilane coupling agent at a reaction temperature of 80° C. for 20 min; S2, taking 20% ​​of the oligomer polyol, mixing it with the epoxy resin and the material obtained in step S1, and dehydrating it; S3, mixing diisocyanate, 80% of oligomer polyol, and a catalyst, reacting at a reaction temperature of 65° C. for a reaction time of 1 h to obtain a polyurethane prepolymer; S4, mixing the mixed material obtained in step S2 and the polyurethane prepolymer obtained in step S3, reacting at a reaction temperature of 80° C. for 4 hours to obtain a TPU material, laminating the TPU material into sheets, punching and forming, and obtaining the wear-resistant and environmentally friendly TPU sheet for the car mat.

[0058] The silicon dioxide in this embodiment is micron-sized silicon dioxide with an average particle size of 6 microns.

[0059] Embodiment 11 The difference between this embodiment and embodiment 8 is that the amount of silicon dioxide in this embodiment is 7 parts.

[0060] Example 12 The difference between this embodiment and embodiment 8 is that the amount of silicon dioxide in this embodiment is 8 parts.

[0061] Embodiment 13 The difference between this embodiment and embodiment 11 is that this embodiment uses an equal amount of nano-silicon dioxide to replace silicon dioxide. The average particle size of the nano-silicon dioxide in this embodiment is 5-10 nm.

[0062] The experimental test results of Examples 10-13 are shown in Table 4.

[0063] Table 4 - Experimental test results of Examples 10-13 Example Wear amount (mg) Tensile strength(MPa) Example 8 8.3 79.2 Example 10 7.0 80.3 Embodiment 11 6.7 80.9 Example 12 6.9 80.2 Embodiment 13 5.3 83.4 Result analysis: The difference between Examples 10-13 and Example 8 is that silicon dioxide is also added when preparing the wear-resistant and environmentally friendly TPU for car mats. Combined with the experimental test results in Table 4, it can be seen that the addition of silicon dioxide can further improve the tensile strength and wear resistance of the prepared wear-resistant and environmentally friendly TPU for car mats.

[0064] The difference between Example 13 and Example 11 is that an equal amount of silicon dioxide is used to replace nano-silicon dioxide when preparing the wear-resistant and environmentally friendly TPU for automobile floor mats. Combined with the experimental test results in Table 4, it can be seen that nano-silicon dioxide can further improve the tensile strength and wear resistance of the prepared TPU.

[0065] Examples 14-15 Embodiment 14 The difference between this embodiment and embodiment 13 is that the preparation parameters in preparing the wear-resistant and environmentally friendly TPU for automobile mats are different, and the difference is as follows: S1, mixing and reacting the fiber composite, hollow glass microspheres, nano-silica and aminosilane coupling agent at a reaction temperature of 90° C. for 25 min; S2, taking 30% of the oligomer polyol, mixing it with the epoxy resin and the material obtained in step S1, and dehydrating it; S3, mixing diisocyanate, 70% of oligomer polyol, and a catalyst, reacting at a reaction temperature of 70° C. for a reaction time of 1.5 h to obtain a polyurethane prepolymer; S4, mixing the mixed material obtained in step S2 and the polyurethane prepolymer obtained in step S3, reacting at a reaction temperature of 85° C. for 5 hours to obtain a TPU material, laminating the TPU material into sheets, punching and forming, and obtaining the wear-resistant and environmentally friendly TPU sheet for the car mat.

[0066] Embodiment 15 The difference between this embodiment and embodiment 13 is that the preparation parameters in preparing the wear-resistant and environmentally friendly TPU for automobile mats are different, and the difference is as follows: S1, mixing and reacting the fiber composite, hollow glass microspheres, nano-silica and aminosilane coupling agent at a reaction temperature of 100° C. for 30 min; S2, taking 40% of the oligomer polyol, mixing it with the epoxy resin and the material obtained in step S1, and dehydrating it; S3, mixing diisocyanate, 60% oligomer polyol, and a catalyst, reacting at a reaction temperature of 75° C. for a reaction time of 2 h to obtain a polyurethane prepolymer; S4, mixing the mixed material obtained in step S2 and the polyurethane prepolymer obtained in step S3, reacting at a reaction temperature of 90° C. for 6 hours to obtain a TPU material, laminating the TPU material into sheets, punching and forming, and obtaining the wear-resistant and environmentally friendly TPU sheet for the car mat.

[0067] The experimental test results of Examples 14-15 are shown in Table 5.

[0068] Table 5 - Experimental test results of Examples 14-15 Example <![CDATA[Wear amount (mm 3 )]]> Tensile strength(MPa) Embodiment 13 5.3 83.4 Embodiment 14 4.8 84.9 Embodiment 15 5.0 84.5 Result analysis: The difference between Examples 14-15 and Example 13 is that the preparation parameters are different when preparing the wear-resistant and environmentally friendly TPU for automobile floor mats. Combined with the experimental test results in Table 5, it can be seen that the wear-resistant and environmentally friendly TPU for automobile floor mats prepared by Example 14 has better tensile strength and wear resistance.

[0069] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A wear-resistant and environmentally friendly TPU for car mats, characterized in that: The environmentally friendly TPU includes the following raw materials by weight: 20-30 parts of diisocyanate, 50-80 parts of oligomer polyol, 30-45 parts of epoxy resin, 20-30 parts of fiber composite, 10-15 parts of hollow glass microspheres, 5-8 parts of aminosilane coupling agent and 0.5-1 part of catalyst; the fiber composite includes carbon fiber and steel fiber, wherein the weight ratio of the carbon fiber to the steel fiber is 1:

1.

2. The wear-resistant and environmentally friendly TPU for car mats according to claim 1, characterized in that: The environmentally friendly TPU comprises the following raw materials by weight: 25-30 parts of isocyanate, 65-80 parts of oligomer polyol, 40-45 parts of epoxy resin, 25-30 parts of fiber composite, 12.5-15 parts of hollow glass microspheres, 7-8 parts of aminosilane coupling agent and 0.8-1 part of catalyst.

3. The wear-resistant and environmentally friendly TPU for automobile mats according to claim 1, characterized in that: The isocyanate comprises 28 parts, oligomer polyol 75 parts, epoxy resin 43 parts, fiber composite 28 parts, hollow glass microspheres 14 parts, aminosilane coupling agent 7.4 parts and catalyst 0.9 parts.

4. The wear-resistant and environmentally friendly TPU for automobile mats according to claim 1, characterized in that: The environmentally friendly TPU also includes 5-8 parts of silicon dioxide.

5. The wear-resistant and environmentally friendly TPU for automobile mats according to claim 1, characterized in that: The silicon dioxide is nano silicon dioxide; the particle size of the nano silicon dioxide is 5-10nm.

6. The wear-resistant and environmentally friendly TPU for automobile mats according to claim 1, characterized in that: The diameters of the carbon fibers and steel fibers are both 5-10 microns.

7. The wear-resistant and environmentally friendly TPU for automobile mats according to claim 1, characterized in that: The oligomer polyol is polycaprolactone polyol.

8. The wear-resistant and environmentally friendly TPU for automobile mats according to claim 1, characterized in that: The aminosilane coupling agent includes gamma-aminopropyltrimethoxysilane.

9. The wear-resistant and environmentally friendly TPU for automobile mats according to claim 1, characterized in that: The catalyst includes triethanolamine.

10. A method for preparing the wear-resistant and environmentally friendly TPU for automobile mats according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: S1, mixing and reacting the fiber composite, hollow glass microspheres and aminosilane coupling agent, the reaction temperature is 80-100°C, and the reaction time is 20-30min; S2, taking 2040% of the oligomer polyol, mixing it with the epoxy resin and the material obtained in step S1, and dehydrating it; S3, mixing diisocyanate, 60-80% oligomer polyol, and a catalyst, reacting at a reaction temperature of 65-75° C. for 1-2 hours to obtain a polyurethane prepolymer; S4, mixing the mixed material obtained in step S2, the polyurethane prepolymer obtained in step S3 and the remaining raw materials, reacting at a reaction temperature of 80-90° C. for 4-6 hours to obtain a TPU material, pressing the TPU material into a sheet, punching and forming, and obtaining the wear-resistant and environmentally friendly TPU sheet for the car mat.

Citation Information

Patent Citations

  • Thermoplastic polyurethane matrix resin

    CN110746566A

  • TPU antiskid gasket and preparation method thereof

    CN112226066A

  • Wear-resistant sole and manufacturing method thereof

    CN117417582A

  • Thermoplastic polyurethane elastomer based on a hydroxyl terminated polyol, an aromatic chain extender and 1,5 naphthalene diisocyanate

    US5599874A

Cited By

  • Wear-resistant automobile floor mat formulation and preparation method comprising same

    WO2026207770A1